Body Weight Loss and Tissue Wasting in Late Middle-Aged Mice on Slightly Imbalanced Essential/Non-essential Amino Acids Diet - Corsetti, Giovanni; Pasini, Evasio; Romano, Claudia; Calvani, Riccardo; Picca, Anna; Marzetti, Emanuele; Flati, Vincenzo; Dioguardi, Francesco S. (Frontiers in Medicine, 2018)
Objective: Inadequate protein intake can impair protein balance thus leading to skeletal muscle atrophy, impaired body growth, and functional decline. Foods provide both non-essential (NEAAs) and essential amino acids (EAAs) that may convey different metabolic stimuli to specific organs and tissues. In this study, we sought to evaluate the impact of six diets, with various EAA/NEAA blends, on body composition and the risk of developing tissue wasting in late middle-aged male mice. Methods: Six groups of late middle-aged male mice were fed for 35 days with iso-nutrients, iso-caloric and iso-nitrogenous special diets containing different EAA/NEAA ratios ranging from 100%/0% to 0%/100%. One group fed with standard laboratory rodent diet (StD) served as control. Preliminarily, we verified the palatability of the diets by recording the mice preference, and by making accessible all diets simultaneously, in comparison to StD. Body weight, food and water consumption were measured every three days. Blood and urine samples, as well as heart, kidneys, liver, spleen, triceps surae, retroperitoneal WAT, and BAT were harvested and weighed. Results: Mice consuming NEAA-based diets, although showing increased food and calorie intake, suffered the most severe weight loss. Interestingly, the diet containing a EAA/NEAA-imbalance, with moderate NEAAs prevalence, was able to induce catabolic stimuli, generalized body wasting and systemic metabolic alterations comparable to those observed with diet containing NEAA alone. In addition, complete depletion of retroperitoneal white adipose tissue and a severe loss (>75%) of brown adipose tissue were observed together with muscle wasting. Conversely, EAA-containing diets induced significant decreases in body weight by reducing primarily fat reserves, but at the same time they improved the clinical parameters. On these basis we can deduce that tissue wasting was caused by altered AA quality, independent of reduced nitrogen or caloric intake. Conclusion: Our results indicate that diets containing an optimized balance of AA composition is necessary for preserving overall body energy status. These findings are particularly relevant in the context of aging and may be exploited for contrasting its negative correlates, including body wasting.